Termite-affected soils in the Western Cape – a toolkit for the assessment of oxalotrophy and carbon storage potential - Nel, Teneille (Stellenbosch : Stellenbosch University, 2025)
Nel, Teneille. 2024. Termite-affected soils in the Western Cape – a toolkit for the assessment of oxalotrophy and carbon storage potential. Unpublished doctoral dissertation. Stellenbosch : Stellenbosch University [online]. Available: https://scholar.sun.ac.za/handle/10019.1/131859